Influencia de la responsabilidad social empresarial en el comportamiento de compra de los clientes de Plaza Vea Trujillo 2021 - Ventura Lozano, Ericka Lucero (2022)
The purpose of this work was to determine the influence of corporate social responsibility on the purchasing behavior of Plaza Vea Trujillo 2021 customers. The problem was: How does corporate social responsibility influence the purchasing behavior of Plaza Vea Trujillo customers? 2021? A non-experimental cross sectional study with a causal correlational design was developed; the methods used were analytical, synthetic and statistical. The population was considered to be people with the ability to pay in the province of Trujillo and a simple random probabilistic sampling of 394 people was applied. Regarding the technique, the survey was used and the questionnaire as an instrument. The result is that almost 32% of the customers surveyed consider corporate social responsibility an important aspect when choosing where to buy and consequently this affects their purchasing behavior. The conclusion establishes that corporate social responsibility influences the purchasing behavior of Plaza Vea Trujillo customers, since a third of the respondents considered this aspect when choosing their place of purchase, although some took into account other attributes.